(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research aimed to analyze the impact of entrepreneurial characteristics (personal, behavioral, and managerial) on shaping the entrepreneurial intention of female students at the Arab International Private University, focusing on the moderating role of motivational factors (push and pull). The research adopted a descriptive-analytical approach using a field questionnaire and employed hierarchical multiple linear regression to test the interaction among variables. The results revealed that managerial characteristics had the most significant impact on entrepreneurial intention, whereas personal and behavioral characteristics lacked any significant direct effect. Regarding motivators, pull factors (such as ambition and self-actualization) demonstrated both a direct effect and a statistically significant positive moderating role, interacting with entrepreneurial characteristics and amplifying their effectiveness in enhancing intention. Conversely, push factors (such as unemployment and economic pressures) showed no moderating role, acting instead as independent determinants that do not intersect with individual traits. The significance of these findings lies in demonstrating that external motivators are not homogeneous; while push pressures act as an independent coercive force, pull opportunities function as a "catalyst" that interacts with individual readiness. These findings guide higher education institutions to design programs that develop managerial skills and create a conducive "pull" environment that supports independence and provides successful role models, thereby helping female students transform their intentions into sustainable ventures.